Effects of myogenic parametres in water polo realised in different regimes of actual musculature - Guzina, B.; Zrnic, R. (Sport Science - International Scientific Journal of Kinesiology, 2014)
A sample of 25 water polo players of different qualitative level was used to estimate the impact of myogenic abilities and the quality of "scissor" kicks on the power and precision of throwing a water polo ball in the conditions of optimal state of actual musculature, and after the appearance of local fatigue. The assessment of myogenic potentials of selected water polo players was performed by the electronic dynamometer, which, in a specific pool test, registered the force exerted during simulated water polo shooting. The quality of "scissor" kick was indirectly estimated with the help of time spent in the position of jumping out of the water, and the power of elevation was equated with the length reached. Acquired results showed that the maximum force of actual musculature was defined as a significant predictor of the precision of throwing (passing and shooting).Regression analysis proved a significant positive effect of myogenic abilities on the successful performance of water polo elements.In addition, a great impact of "scissor" kicks on the quality of water polo was proved, justifying the importance ascribed to these elements in modern training.